Task-appropriate input supports word–object association in 14-month-old female infants. Issue 2 (10th March 2020) - FAIS, Laurel; VATIKIOTIS-BATESON, Eric
Abstract: Fourteen-month-old infants are unable to link minimal pair nonsense words with novel objects (Stager & Werker, 1997). Might an adult's productions in a word learning context support minimal pair word–object association in these infants? We recorded a mother interacting with her 24-month-old son, and with her 5-month-old son, producing nonsense words bin and din. We used these productions to determine if they had a differential effect on 14-month-old infants' word–object association abilities. Females hearing the words spoken to the older infant, but not those to the younger, succeeded. We suggest that the task-appropriateness of utterances can support infant word learning.